A Practical Guide to Stage Lighting - Shelley, Steven Louis (Taylor and Francis, 2013)
The new edition of the bestselling favorite that you have been waiting for! This is the same nuts-and-bolds look at the construction and implementation of theatrical lighting design that you need, but with a unique focus on design with a combination of theory and application that can't be found anywhere else. A Practical Guide to Stage Lighting has handy step-by-step illustrations of the technical tools and methods used for lighting design along with real life examples showing why some techniques succeed while others fail. With Shelley's Notes, Notes from the Road, and Shelley's Soapbox, this book finds a way to deliver complex information with a lightness and humor that captivates and helps you learn without bogging you down with boring and heavy information. Topics covered: * Defining the parameters that affect any lighting design: the contract, the budget, the type and size of the production, the production schedule, and the performance facility * An analysis of the concepts of light console programming * Setting up * The light plot * Safe construction